Kaufmann desert house. The landscape through the analysis of the architectural composition (2021)
This article links instruments developed for the valuation of the landscape and its usefulness, in the analysis of the architectural composition. The contribution explains the aesthetic categories for the appreciation of the landscape through project operations. For this purpose, Richard Neutra’s Kaufmann house in Palm Springs is studied through a formal analysis, where the results discuss the degree of commensurability in the passage of concepts between disciplines. It is argued that the idea of landscape is a cultural construct that demands to educate the eye for its appreciation. The landscape gives meaning to the architectural composition, fulfilling metaphorically the role of semantics, which together with a form of syntax completes the proposal to have a grammar for learning the architecture project raised in earlier research